2020
DOI: 10.1186/s12944-020-01254-2
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate decreased microalbuminuria in the type 2 diabetes patients with hypertriglyceridemia

Abstract: Background: This study was to research the efficacy of fenofibrate in the treatment of microalbuminuria in the patients with type 2 diabetes mellitus (T2DM) and hypertriglyceridemia. Methods: Type 2 diabetic patients (56) with microalbuminuria and hypertriglyceridemia aged 30 to 75 were randomly divided into the fenofibrate treatment group(n = 28) and the control group (n = 28) for 180 days. Urinary microalbumin /creatinine ratio (UACR) and other metabolic parameters were compared at baseline, during treatment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The DAIS study indicated that fenofibrate prevented the progression to microalbuminuria on a long-term basis in diabetic patients (27). Furthermore, our previous research also found that fenofibrate reduced microalbuminuria in patients with type 2 diabetes (28). In addition, PPAR-α agonists have been demonstrated to prevent DN and reduce proteinuria in both type 1 and type 2 diabetic animals (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 77%
“…The DAIS study indicated that fenofibrate prevented the progression to microalbuminuria on a long-term basis in diabetic patients (27). Furthermore, our previous research also found that fenofibrate reduced microalbuminuria in patients with type 2 diabetes (28). In addition, PPAR-α agonists have been demonstrated to prevent DN and reduce proteinuria in both type 1 and type 2 diabetic animals (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 77%
“…Currently, metabolic diseases have already benefited from the clinical application of PPARα partial agonists, showcasing their significant therapeutic potential. Notably, fenofibrate, for instance, has emerged as an effective treatment for diabetes [114,115]. Moreover, several PPARα agonists have exhibited promising outcomes in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the decrease in uric acid, TG, and UACR was greater at 180 days in the fenofibrate group than in the control group (P<0.05 for all). A decrease in UACR was positively associated with the decreases in TG (P=0.042) and uric acid (P=0.024) in the fenofibrate group [60]. Likewise, the recent ACCORD-Lipid trial analysis showed that the fenofibrate therapy caused more transitory worsening of eGFR events but slowed long-term eGFR decrease [42].…”
Section: Diabetic Nephropathymentioning
confidence: 92%